Pengaruh Kecerdasan Interpersonal Dan Kecerdasan Logis-Matematis Terhadap Kemampuan Penalaran Matematis Siswa - Kartono; Dodi Priandi; KMA Fauzi Sinambela (Universitas Asahan, 2026)
This study aims to examine the effect of interpersonal intelligence (X1) and logical–mathematical intelligence (X2) on students’ mathematical reasoning ability (Y) of grade XI MIPA students at SMA Negeri 1 Pematang Bandar. This research employed a quantitative approach with a correlational design. The sample consisted of 72 students selected using proportional random sampling. Data on interpersonal intelligence were collected using a questionnaire, while logical–mathematical intelligence and mathematical reasoning ability were measured using essay tests. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 21 after passing prerequisite tests including normality and linearity tests. The results showed that interpersonal intelligence had a positive and significant effect on mathematical reasoning ability (t = 3.418, p < 0.05), and logical–mathematical intelligence also had a positive and significant effect on mathematical reasoning ability (t = 6.613, p < 0.05). Simultaneously, interpersonal intelligence and logical–mathematical intelligence significantly influenced mathematical reasoning ability (F = 33.215, p < 0.05). The coefficient of determination showed R² = 0.491, indicating that 49.1% of the variance in students’ mathematical reasoning ability was explained by interpersonal intelligence and logical–mathematical intelligence. These findings indicate that both interpersonal and logical–mathematical intelligence play an important role in improving students’ mathematical reasoning ability.